2014
DOI: 10.4040/jkan.2014.44.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Progressive Walking Program on Physical Activity, Exercise Tolerance, Recovery, and Post-Operative Complications in Patients with a Lung Resection

Abstract: 연구의 필요성폐암은Purpose: The purpose of this study was to identify the effects of a Progressive Walking program (PW) on physical activity, exercise tolerance, recovery, and post-operative complications for patients with a lung resection. Methods: A nonequivalent control group non-synchronized design was utilized and 37 participants with a lung resection (22 for control group, 15 for experimental group) were recruited at A university hospital from December 2012 to August 2013. The PW consisted of preoperative educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(8 reference statements)
0
2
0
2
Order By: Relevance
“…The efficacy of a step-setting strategy in facilitating early ambulation received further validation in the work of Kim and Lee. 36 Moreover, guidelines 37 advocate for the establishment of a daily ambulation step count as a means to expedite gastrointestinal recovery and mitigate the risk of ileus. Several studies have employed electronic pedometers to track ambulation among patients undergoing abdominal and gynaecological surgeries, 28 38 with findings indicating a significant increase in early patient mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a step-setting strategy in facilitating early ambulation received further validation in the work of Kim and Lee. 36 Moreover, guidelines 37 advocate for the establishment of a daily ambulation step count as a means to expedite gastrointestinal recovery and mitigate the risk of ileus. Several studies have employed electronic pedometers to track ambulation among patients undergoing abdominal and gynaecological surgeries, 28 38 with findings indicating a significant increase in early patient mobility.…”
Section: Discussionmentioning
confidence: 99%
“…This positive effect has also been described in other disciplines. Kim and Lee 17 reported that a postoperative walking program improved patients’ health and reduced costs after lung resection. Another study demonstrated that patients with impaired mobility had less improvement in weight‐related co‐morbidities after bariatric surgery 12 …”
Section: Discussionmentioning
confidence: 99%
“…Kim and Lee 17 reported that a postoperative walking program improved patients' health and reduced costs after lung resection.…”
Section: Discussionmentioning
confidence: 99%
“…3개의 연구는 노력성 폐활량(forced vital capacity, FVC)을 변수로 제시하였다 14,22,24) . 그러나 FEV의 평균 차 24) , FEV의 정상치 대비 비율 14) , 15,16,17,19,21,[24][25][26] . 이와 더불어 최대 산소 흡기량(maximum oxygen consumption, VO 2peak )을 2개의 연구에서 분석에 활용하였다 13,25) .…”
Section: 하지만unclassified
“…4개 모두 신체건강영역(physical component summary, PCS)과 정신건강영역(mental component summary, MCS) 삶의 질을 모두 제시하였는데 이 중 2개의 연구는 해당 영역의 산출 값을 제시한 반면 25,26) , 나 머지 2개의 연구는 해당 영역의 중재 전후 차이 값을 제 시하였다 23,24) . 기타 EORTC quality of life questionnairelung cancer 13 19) , World Health Organization Quality of 5개의 연구에서 안전성을 평가하여 보고하였다 13,21,22,24,26) .…”
Section: 하지만unclassified